Expanding Alternative Splicing Identification by Integrating Multiple Sources of Transcription Data in Tomato - Clark, Sarah; Yu, Feng; Gu, Lianfeng; Min, Xiang Jia (Frontiers in Plant Science, 2019)
Tomato (Solanum lycopersicum) is an important vegetable and fruit crop. Its genome has been completely sequenced and there are also a large amount of available expressed sequence tags (ESTs) and short reads generated by RNA sequencing (RNA-seq) technologies. Mapping transcripts including mRNA sequences, ESTs, and RNA-seq reads to the genome allows identifying pre-mRNA alternative splicing (AS), a post-transcriptional process generating two or more RNA isoforms from one pre-mRNA transcript. We comprehensively analyzed the AS landscape in tomato by integrating genome mapping information of all available mRNA and ESTs with mapping information of RNA-seq reads which were collected from 27 published projects. A total of 369,911 AS events were identified from 34,419 genomic loci involving 161,913 transcripts. Within the basic AS events, intron retention is the prevalent type (18.9%), followed by alternative acceptor site (12.9%) and alternative donor site (7.3%), with exon skipping as the least type (6.0%). Complex AS types having two or more basic event accounted for 54.9% of total AS events. Within 35,768 annotated protein-coding gene models, 23,233 gene models were found having pre-mRNAs generating AS isoform transcripts. Thus the estimated AS rate was 65.0% in tomato. The list of identified AS genes with their corresponding transcript isoforms serves as a catalog for further detailed examination of gene functions in tomato biology. In addition, a large number of non-coding RNAs were also identified in the work. The post-transcriptional information is also expected to be useful in improving the predicted gene models in tomato. The sequence and annotation information can be accessed at Plant Alternative Splicing Database (http://proteomics.ysu.edu/altsplice). .